Horan, Sharon. Questionnaire. Sharon writes about her career as an occupational therapist in Newfoundland and Labrador 1987-2022 - Manojlovich, Mary (2022)
Sharon completed a questionnaire including her educational and work history; memories of early years working in NL; highlights of her career.